2008
DOI: 10.1002/rcm.3671
|View full text |Cite
|
Sign up to set email alerts
|

The utility of ultra‐performance liquid chromatography/electrospray ionisation time‐of‐flight mass spectrometry for multi‐residue determination of pesticides in strawberry

Abstract: The utility of ultra-performance liquid chromatography/orthogonal-acceleration time-of flight mass spectrometry (UPLC/TOFMS) for the rapid qualitative and quantitative analysis of 100 pesticides targeted in strawberry was assessed by comparing results with those obtained using a validated in-house UPLC tandem mass spectrometry (MS/MS) multi-residue method. Crude extracts from retail strawberry samples received as part of the 2007 annual UK pesticide residues in food surveillance programme were screened for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…A comparison between LC-MS/MS and UPLC-MS/MS chromatograms of apple crude extract spiked with 17 pesticides is illustrated in Figure 1, which clearly demonstrates the gains in analysis time and resolution using UPLC. Applications of UPLC hyphenated with TOF-MS (Taylor et al, 2008) and QqTOF-MS (Picó et al, 2007bWang & Leung, 2009) for pesticide residues analysis have been also reported.…”
Section: Liquid Chromatographymentioning
confidence: 98%
See 3 more Smart Citations
“…A comparison between LC-MS/MS and UPLC-MS/MS chromatograms of apple crude extract spiked with 17 pesticides is illustrated in Figure 1, which clearly demonstrates the gains in analysis time and resolution using UPLC. Applications of UPLC hyphenated with TOF-MS (Taylor et al, 2008) and QqTOF-MS (Picó et al, 2007bWang & Leung, 2009) for pesticide residues analysis have been also reported.…”
Section: Liquid Chromatographymentioning
confidence: 98%
“…In another direct comparison for the determination of 16 pesticides and transformation products in baby foods, UPLC yielded enhanced S/N ratios, narrower peaks and decreased analysis times over HPLC (Leandro et al, 2006). UPLC-QqQ-MS in multi-residue analysis of pesticides aims to increase the number of monitored compounds, reduce the time of the LC separation step and improve the performance characteristics of the determination step (Lambropoulou & Albanis, 2007;Leandro et al, 2007b;Pozo et al, 2007;Gervais et al, 2008;Kovalczuk et al, 2008;Marín et al, 2009;Mol et al, 2008;Taylor et al, 2008;Wang & Leung, 2009). More than 50 pesticides have been determined in alcoholic beverages by UPLC-QqQ-MS in a run time of 11 min acquiring two transitions per analyte (Plaza Bolãnos et al, 2008) while 90 pesticides have been determined in fruit juices by UPLC-QqQ-MS in MRM mode, in the same run time of 11 min (Romero-González, .…”
Section: Liquid Chromatographymentioning
confidence: 98%
See 2 more Smart Citations
“…Its separation efficiency, up to 40,000, considerably exceeds the separation efficiency of the quadrupole analyzer. In the analysis of pesticide residues in food, the time-of-flight analyzer is mainly used to confirm the presence of the compounds of interest in matrices such as fruit and vegetables (Mezcua et al 2009;Taylor et al 2008), honey and meat (Mol et al 2008), fruit beverages GarciaReyes et al 2008), and wine (Perez-Ortega et al 2012).…”
Section: Time-of-flight Analyzermentioning
confidence: 99%